2021
DOI: 10.1371/journal.pone.0243407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum bilirubin levels, urinary biopyrrin levels, and retinopathy in patients with diabetes

Abstract: Objective Previous reports have indicated that serum bilirubin levels may be associated with diabetic retinopathy. However, the detailed mechanism is not fully understood. In this study, we evaluated the relationship between the severity of diabetic retinopathy and various factors including bilirubin levels and factors influencing bilirubin metabolism. Methods The study participants consisted of 94 consecutive patients with diabetes mellitus admitted to Kyushu University Hospital from April 2011 to July 2012… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Bilirubin is a strong endogenous antioxidant [6]. Accumulating evidence has shown the relationship between serum bilirubin levels and oxidative stress-related diseases such as diabetes, diabetic nephropathy, and cardiovascular diseases [7][8][9][10][11][12]. In addition, in the previous report, we showed that serum levels of bilirubin is a strong predictive biomarker for ADL disability in older patients with diabetes (aged 70 years and over) [13].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Bilirubin is a strong endogenous antioxidant [6]. Accumulating evidence has shown the relationship between serum bilirubin levels and oxidative stress-related diseases such as diabetes, diabetic nephropathy, and cardiovascular diseases [7][8][9][10][11][12]. In addition, in the previous report, we showed that serum levels of bilirubin is a strong predictive biomarker for ADL disability in older patients with diabetes (aged 70 years and over) [13].…”
Section: Introductionmentioning
confidence: 60%
“…Bilirubin is a strong endogenous antioxidant. Many epidemiological and animal studies have shown that serum bilirubin levels are inversely associated with the onset and development of oxidative stress-related diseases including diabetes, diabetic vascular complications, chronic kidney disease (CKD), and cardiovascular diseases [7][8][9][10][11][12]. Therefore, it is most likely that the negative relationship between serum indirect bilirubin levels and the skeletal muscle mass in male old-old patients with type 2 diabetes is due to the decreased antioxidative activity and subsequent increased oxidative stress.…”
Section: Plos Onementioning
confidence: 99%
“…Biopyrrins served as markers of oxidative stress in various studies. The inherent biological activity of these oxidation products is still not understood. Structurally related tripyrrindiones also suggest interesting chemical properties for this class of molecules .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our ndings, a study including 336 patients with T2DM demonstrated that serum bilirubin was dramatically higher in the patients without DR than in those with PDR (p < 0.05)(18). Additionally, Kudo et al found that serum bilirubin levels decreased as the severity of retinopathy increased (39). Therefore, it is suggested that serum bilirubin not only was a simple indicator to evaluate the risk of DR, but also might be a reliable indicator of DR progression in clinical practice.…”
Section: Discussionmentioning
confidence: 99%